2003
DOI: 10.1073/pnas.0337680100
|View full text |Cite
|
Sign up to set email alerts
|

Designed to be stable: Crystal structure of a consensus ankyrin repeat protein

Abstract: Ankyrin repeat (AR) proteins mediate innumerable protein-protein interactions in virtually all phyla. This finding suggested the use of AR proteins as designed binding molecules. Based on sequence and structural analyses, we designed a consensus AR with fixed framework and randomized interacting residues. We generated several combinatorial libraries of AR proteins consisting of defined numbers of this repeat. Randomly chosen library members are expressed in soluble form in the cytoplasm of Escherichia coli con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
285
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(295 citation statements)
references
References 54 publications
9
285
0
1
Order By: Relevance
“…Hence, one might think that AR proteins differ from globular proteins in folding and stability and each AR in a protein could unfold and refold individually. However, folding studies on INK4 proteins (12,17,23,32,33), Notch AR domain (34,35), myotrophin (22), and some engineered AR proteins (14,15,36,37) have demonstrated that AR proteins exhibit an equilibrium two-state transition between native and unfolded proteins by spectroscopic and calorimetric criteria, similar to most globular proteins. Furthermore, no partially folded intermediates have been found in these equilibrium folding-unfolding reactions, except that a NMR study of p19 in the presence of moderate concentrations of urea revealed the possible existence of an equilibrium intermediate with poor chemical shift dispersions, suggesting that it is largely unfolded (32).…”
Section: Folding and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, one might think that AR proteins differ from globular proteins in folding and stability and each AR in a protein could unfold and refold individually. However, folding studies on INK4 proteins (12,17,23,32,33), Notch AR domain (34,35), myotrophin (22), and some engineered AR proteins (14,15,36,37) have demonstrated that AR proteins exhibit an equilibrium two-state transition between native and unfolded proteins by spectroscopic and calorimetric criteria, similar to most globular proteins. Furthermore, no partially folded intermediates have been found in these equilibrium folding-unfolding reactions, except that a NMR study of p19 in the presence of moderate concentrations of urea revealed the possible existence of an equilibrium intermediate with poor chemical shift dispersions, suggesting that it is largely unfolded (32).…”
Section: Folding and Stabilitymentioning
confidence: 99%
“…In the third approach, consensus design was combined with a combinatorial library to generate AR proteins containing a common structural framework and novel binding specificities (15,36,(80)(81)(82) (Figures 1a and 6c). For binding scaffolds such as AR proteins, its diversity in binding specificity reflects its diversity in function.…”
Section: Consensus Design and Combinatorial Library Of Arsmentioning
confidence: 99%
“…High resolution crystal structures revealed that proteins containing up to five consensus ankyrin repeats [25,41] and up to eight consensus TPR repeats [42] adopt folds that have root-mean-square-deviations of around 0.9 and 1.6Å, respectively, from analogous structures of naturally-occurring repeat proteins. Thus, structurally speaking, this simple consensus method for repeat-protein design is highly successful.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…DARPins were produced in the E. coli XL10 Gold strain with the pQE30 expression plasmid with isopropyl ␤-D-1-thiogalactopyranoside (IPTG) induction and purified using Ninitrilotriacetic acid (NTA) affinity chromatography as described previously (45). The DARPin proteins obtained were checked by size exclusion chromatography coupled to multiangle light scattering (SEC-MALS) for the oligomerization state.…”
Section: Reagentsmentioning
confidence: 99%